The Application of Diversion for Children as Perpetrators of Criminal Offenses During the Investigation Phase (A Study at the Cirebon City Police Station) - Dea Viqi Alayda Alamsyah; Ismayana Ismayana (International Journal Labs, 2026)
This research examines the implementation of diversion in handling juvenile cases at the investigation stage at the Cirebon City Police Department. The increasing involvement of children in criminal offences indicates that punitive approaches are no longer sufficient, making diversion — as a component of restorative justice — an important alternative. Diversion aims to resolve cases outside formal court proceedings while prioritising the best interests of the child and their social recovery. This research employs an empirical legal method with a socio-juridical approach, combining legal analysis with field data. Data were collected through interviews with investigators and supported by relevant legal literature and regulations. The findings reveal that diversion has been applied, though not consistently. Some cases are successfully resolved through diversion, while others proceed to formal judicial processes or are settled at the preliminary stage without formal diversion mechanisms. Several obstacles affect its implementation, including resistance from victims, public perceptions favouring punitive responses, limited understanding of restorative justice among law enforcement officers, and inadequate facilities. In conclusion, the implementation of diversion at the investigation stage remains in a transitional phase toward a fully restorative justice approach. Strengthening institutional capacity, improving public awareness, and enhancing coordination among stakeholders are necessary to ensure the effective application of diversion within the juvenile criminal justice system.